Bridge fires in the 21st century: A literature review. (December 2021) - Hu, Jiayu; Carvel, Ricky; Usmani, Asif
Abstract: Bridge failures due to fires are more common than failures due to extreme weather or earthquakes. Yet, unlike wind and earthquake loading, fire does not receive the same level of attention. Major 21st Century fire incidents involving bridges are listed and discussed. Various methods by which fire could be considered in design are reviewed and discussed. Sources of fire test data, which include only one full scale fire test to-date, are provided. It is hoped that by considering these factors, codes, standards and engineering practice could be updated to include consideration of fire in routine bridge design. Highlights: Bridge fire accidents are not as rare as might be generally perceived, when compared to earthquakes or floods. The most severe damage is caused by accidents under the bridge. The government could focus on setting up regulations for only the bridges with span larger than 5 m. The standards and engineering practice should be updated to include consideration of fire load in routine bridge design.